INISIASI PENGEMBANGAN DESA NGESREPBALONG SEBAGAI SENTRA ALPUKAT BERBASIS GREEN ECONOMY DI KABUPATEN KENDAL, JAWA TENGAH - Retnoningsih, Amin; Ngabiyanto, Ngabiyanto; Triwibowo, Bayu; Hadiyanti, Luthfia Nur; Solichin, Solichin; Laraswati, Vivi Anggraeni; Rizki, Angela Dita; Sa’adah, Nur (Universitas Padjadjaran, 2024)
The initiation of the development of Ngesrepbalong Village as a green economy-based avocado center is supported by the village's regional conditions. A green economy needs to be implemented because Ngesrepbalong is known to be the only village in Kendal Regency that has the potential for landslides. Landslide mitigation can be done by increasing the population of deep-rooted, compact, and massive woody trees such as avocados so that water can be retained and the soil becomes stable. The priority problems of the Gunungsari farmer partners in Ngesrepbalong Village include management and production aspects of preparing their area as an avocado center area. Farmer group institutions have yet to be available, and most avocados are not superior varieties. This activity aims to initiate Ngesrepbalong as a green economy-based avocado center. Activities will occur in May-November 2023 through socialization, training and mentoring, application of technology and mentoring, monitoring and evaluation, and sustainability program. The institution of superior avocado farmers was realized by forming the